Bridging Therapies are not Detrimental in Patients with Hepatocellular Cancer waiting for Liver Transplant: A Propensity Score Analysis. (July 2018) - Lai, Quirino; Cillo, Umberto; Iesari, Samuele; Finkenstedt, Armin; Rossi, Massimo; Tsochatzis, Emmanuil; Otto, Gerd; Ettorre, Giuseppe M; Tisone, Giuseppe; Vivarelli, Marco; Avolio, Alfonso W; Foguenne, Maxime; et al.
Abstract : EURHECA-LT. Patients with hepatocellular cancer (HCC) within Milan Criteria (MC) waiting for liver transplantation (LT) are approached in two different ways: direct LT vs. first treating the tumour using LRT. In these patients, the usefulness of LRT is still questioned. To investigate the role of LRT in patients with MC-IN HCC waiting for LT in terms of risk of de-listing, intention-to-treat (ITT) survival and post-LT recurrence. The EurHeCaLT database allowed to identify 1, 177 MC-IN HCC patients listed for possible LT. Using propensity score matching, two homogeneous groups of directly transplanted (n=205) vs. firstly LRT treated patients (n=205) were studied. Median follow-up period was 3.6 years (IQR: 1.5-7.5). Comparing the groups, only two differences were observed, namely a longer median waiting time in the LRT-first group (5vs.4 months; p=0.04) and a greater median dimension of the target lesion at the moment of LT or de-listing in the direct-LT group (2.0vs.1.7 cm; p<0.0001). At multivariate Cox regression analysis, three independent risk factors for ITT-death were identified: MELD (HR=1.04; p=0.005), radiological progression beyond MC (HR=2.04; p=0.03) and alpha-fetoprotein slope >15ng/mL/month (HR=1.75; p=0.03). At multivariate analysis, multimodal LRT approach (HR=3.18; p=0.01) and maximal diameter of the main HCC lesion (HR=1.53; p=0.045) were independent risk factors for post-LT recurrence. Repetitive LRT was not a significant risk factor in both the analyses. Survival over one year in de-listed patients was more common in LRT-first cases (5.9vs.1.0%; p=0.01). The use of (repetitive) LRT has no detrimental effect in MC-IN patients waiting for LT. LRT represents a tool allowing to further optimize the liver allocation process by selecting patients presenting a high-risk for drop-out (avoiding thereby futile liver transplants). The biological tumor response to the LRT is more than the LRT itself the strongest predictor of intention-to-treat survival and recurrence.